Síntese enzimática de biosurfactante e sua aplicabilidade na indústria do petróleo - Medeiros, Suzan Ialy Gomes de (Universidade Federal do Rio Grande do Norte, 2014)
Enzymes have been widely used in biosynthesis/transformation of organic compounds in substitution the classic synthetic methods. This work is the first writing in literature of enzymatic synthesis for attainment the biossurfactants, the use glucose sucrose, ricinoleic acid e castor oil as substratum, and as biocatalyst, used immobilized lipase Thermomyces lanuginose, Rhizomucor miehei and the Candida antarctica lipase B; alkaline protease and neutral protease from Bacillus subtillis and yeast Saccharomyces cerevisiaeI. The analysis of HPLC (high performance liquid chromatography) showed that highest conversions were reached of used the alkaline protease from Bacillus subtillis. Laboratory tests, to evaluate the applicability, indicated that the produced biosurfactantes had good stability in presence of salts (NaCl) and temperature (55 e 25°C), they are effective in the reduction of the superficial tension and contac angle, but they have little foaming capacity, when compared with traditional detergents. These results suggest that the prepared surfactants have potential application as wetting agent and perforation fluid stabilizer Enzimas têm sido largamente utilizadas em mações de compostos orgânicos em substituição aos métodos sintéticos clássicos. Esta dissertação de mestrado é o primeiro relato escrito em literatura de síntese enzimática para obtenção de biosurfactantes utilizando como substratos glicose, ácido ricinoléico e óleo de mamona, e como biocatalizador, foram empregadas lipases imobilizadas (Thermomyces lanuginosa, Rhizomucor miehei e Candida antarctica B), proteases (Bacillus subtillis alcalina e Bacillus subtillis neutra) e levedura (Saccharomyces cerevisiae). A análise por CLAE (cromatografia líquida de alta eficiência) mostrou que maiores conversões foram alcançadas pelo uso da Bacillus subtillis alcalina. Testes de laboratório, para avaliar sua aplicabilidade, indicaram que os biosurfactantes produzidos apresentam boa estabilidade em presença de NaCl e temperaturas de 55 e 25ºC, são efetivos ...